1979
DOI: 10.1111/j.1751-1097.1979.tb07372.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response Characteristics of Immunologic Unresponsiveness to Uv‐induced Tumors Produced by Uv Irradiation of Mice

Abstract: Abstract— Irradiation of mice with unfiltered FS40 sunlamps renders them susceptible to challenge with highly antigenic UV‐induced skin tumors. Dose‐response studies demonstrated that the susceptibility of mice to tumor challenge was directly proportional to the total dose of UV radiation, and was independent of the manner in which the dose was administered. A fractionated dose was no more effective than the same total dose given as a single treatment in inducing susceptibility to tumor challenge. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 12 publications
(4 reference statements)
0
28
1
Order By: Relevance
“…This is contrary to reports in which conclusions are based on UV radiation-induced reductions in ETAF/IL-1 levels from in vitro experiments (37,38 (41). It has recently been reported that unirradiated skin from highdose UV radiation-exposed animals has normal Langerhans cell density and function (42) and, further, that the antigenpresenting cell defect described to be present in the spleens of UV radiation-exposed mice is due to the migration of such a cell from this central lymphoid compartment to peripheral sites (29).…”
Section: Discussioncontrasting
confidence: 99%
“…This is contrary to reports in which conclusions are based on UV radiation-induced reductions in ETAF/IL-1 levels from in vitro experiments (37,38 (41). It has recently been reported that unirradiated skin from highdose UV radiation-exposed animals has normal Langerhans cell density and function (42) and, further, that the antigenpresenting cell defect described to be present in the spleens of UV radiation-exposed mice is due to the migration of such a cell from this central lymphoid compartment to peripheral sites (29).…”
Section: Discussioncontrasting
confidence: 99%
“…UV suppression of CHS has been shown in humans (Hersey et al 1983;Kalimo et al 1983;Cooper et al 1992) as well as in experimental animals, indicating that this mechanism is relevant to human health. UVB-induced immune suppression is of potential importance in modulation of the immune response in UV-related diseases, e.g., skin cancer (Fisher and Kripke 1977;De Fabo and Kripke 1979;De Fabo and Kripke 1980) and certain infectious diseases (Giannini 1986;Howie et al 1986;Jeevan and Kripke 1989). We have previously demonstrated three phenotypes: namely, high, low, and intermediate susceptibility to UV suppression, based on UV dose-responses for suppression of CHS in 18 strains and substrains of inbred mice (Noonan and Hoffman 1994).…”
Section: Inmxluetlonmentioning
confidence: 99%
“…We have previously found a major difference in susceptibility to UVB suppression between mouse strains, BALB/c mice requiring nearly six times more UV than C57BL/6 mice for 50% suppression of CHS . Because of the potential role of UVB-induced immune suppression in modulation of the immune response to environmental antigens and in UV-related diseases, e.g., skin cancer (Daynes and Spellman 1977;De Fabo and Kripke 1979;De Fabo and Kripke 1980;Fisher and Kripke 1977;Fisher and Kripke 1982), we have investigated further the differences in susceptibility to UV suppression between inbred mouse strains as an initial step in addressing the question of genetic control of this trait.…”
Section: Introductionmentioning
confidence: 99%